ANALYSIS OF 6-FREQUENCY SIMULTANEOUS OBSERVATIONS OF 170 COMPACT EXTRAGALACTIC OBJECTS IN 1995 1996: A STATISTICS OF MAIN SPECTRA PARAMETERS - Kovalev, Yu. Y. (Одеські астрономічні публікації, 2017)
Results of instantaneous spectra observations, carred out at the RATAN-600 during six sets in 1995-1996, are used. We analyse a behaviour of an effective width of spectra, turnover frequency and maximal flux density.